O processo de socialização e construção de identidade profissional do professor iniciante de química - Furlan, Elaine Gomes Matheus (2011)
The present work had as objectives: to widen the comprehension about the formation of teachers by means of a study in the perspective of the beginning Chemistry teacher, focusing on the ingression conditions to the teaching career, its process of socialization and professional identity construction; to investigate the learning of the profession by these acting teachers in high school, considering the particularities of this step in the elementary school; to compare how this process works in the public and private schools of Araraquara/SP. Based on theoretical references that, on one hand, discuss questions related to the scholar culture, such as Pérez Gómez (1998) and Julia (2001) and, on the other hand, relate to aspects about socialization and professional identity construction such as Berger and Luckmann (2007) and Dubar (2005), the research tries to figure out how the process of socialization and professional identity construction works for the beginning Chemistry teachers in a new scholar environment, involving the transmission of scholar culture, its rules, hierarchy, values, rituals and powers, by the other agents of the school. The following hypothesis guided the study: a) there is an installed, sedimented culture and different in each scholar organization, with some common aspects and others may vary, which is evidenced in the socialization process of the pairs, mainly regarding the beginning teachers; b) there is significant difference between the high school from private and public schools, mainly regarding the forms of organization, levels of freedom and autonomy, influencing the interactions that the actors establish among themselves and, consequently, in the construction of their professional identities; c) the operational construction of identity also implies on the acquisition of legitimate knowledge that permit the elaboration of practical strategies and the affirmation of a recognized identity, involving the sharing of the language, codes and its use in direct relations, promoting stable as well as provisory results of socialization processes; d) the beginning teachers are taken to endorse or to refuse the identification that they receive from institutions and from the relation with peers and other actors from the school, according to the paths (biographical and relational) lived throughout their pathway. It is an empirical research, of qualitative nature, whose methodology includes the use of questionnaires to carry out preliminary studies aiming the survey of all 29 high schools (15 public/state and 14 private) in the city of Araraquara/SP, the elaboration of a profile of the 42 Chemistry teachers and the identification of the 14 beginning teachers, besides in-depth interviews with these beginning teachers. The data, collected from 2008-2009, was mapped, organized in charts and tables and analyzed with the aid of the following analysis categories: personal and familiar characteristics of the teachers; informal education, personal and social life; formal education and experiences from the scholar environment; the course of graduation in Chemistry and its preparation for the profession; the teaching profession and the beginning chemistry teacher; the work of the beginning Chemistry teacher (and its deployments), the process of socialization in the scholar environment and the interaction with the school s culture. The results obtained confirmed the hypothesis and allow us to affirm that the socialization processes involve individual and collective aspects, stable and provisory and result in the identities of the beginning Chemistry teachers which are marked by the duality of the relational and biographical processes facing the scholar culture